Potenciais marcadores de tipicidade aromática de vinhos tropicais do Vale do São Francisco em processo de indicação geográfica - Morais, Samara de Macêdo (2020)
The São Francisco Valley (VSF), the second largest wine producing region in Brazil, presents a differentiated viticulture, since it is located at the caatinga biome, with particularities such as: tropical semi-arid climate, high rate of solar radiation, low rainfall and water available for irrigation. These particularities allow the staggered production of grapes, with two harvests per year, in the same vineyard, and the consequent elaboration of fine still and sparkling wines with a chemical composition that includes a diversity of compounds, of which the volatile ones confer authenticity and quality to the drink. In this context, this research had as main objective to identify volatile chemical markers to typify the select group of red and sparkling wines that are part of the process of obtaining the Geographical Indication (GI) VSF. In view of the above, the profile of volatile compounds of these wines, 4 sparkling and 9 red, was determined by microextraction in solid phase in headspace mode associated with the technique of gas chromatography coupled to mass spectrometry (HS-SPME/GC/MS), whose results were evaluated by multivariate statistical analysis. In sparkling wines, 109 volatile compounds were identified, classified into 13 chemical groups, of which the esters, terpenes and alcohols were the majority. Of the total, 33 compounds were identified in all sparkling wines, some compounds with more expressive area representation were identified exclusively in the different types of sparkling wine, being a total of 23 in muscatel, 9 in brut, 5 in brut rosé and 4 in demi-sec, with emphasis on compounds 2-phenyl-undecane, 3-methyl-4-heptanol, 4-phenyl-undecane and germacrene B, identified for the first time in sparkling wines from VSF. The results of sparkling wines indicated a strong association of grape varieties and technological processes of winemaking. In red wines 103 volatile compounds were identified, classified into 13 chemical groups of which the esters and alcohols were the major groups. Of the total of compounds, 27 were identified in all red wines, the cultivars influenced the distinction of volatiles expressed exclusively in only one type of wine. Of the 103 compounds identified in red wines, 22 stood out for their first identification in wines from VSF, like the aromatic 3-phenyl-undecane and 4-phenyl-decane. In this context, the volatile profiles of the commercial sparkling and red wines of the VSF presented possible markers of typicity that can be useful for traceability and indispensable for confirming the authenticity and typicity of wines of this region, necessary prerequisites to assist in the GI structuring process.